Research on topology and control strategy of distribution network flexible interconnected device based on single-phase control unit and contact switch in series - Lu, Yi; Ding, Chao; Ni, Xiaojun; Qiu, Peng; Shang, Yufei; Wang, Zihan (Frontiers in Energy Research, 2025)
There is an urgent need for flexible interconnection in the distribution network. However, due to the complex topology, control strategy and development cost of the existing flexible interconnected device (FID), the existing FID is difficult to be popularized and applied in the above scenarios. In view of the above problems, this paper constructs the FID topology based on the series connection of single-phase control unit and contact switch, and constructs the equivalent circuit of the interconnection line between FID and contact switch in series. The working principle of FID flexible closing loop and power flow control is studied from the dimension of FID output voltage and equivalent impedance. The FID flexible closing loop energy extraction strategy is proposed, and the FID system-level and device-level control strategies with flexible closing loop and power flow control functions are proposed. The simulation results show that the flexible interconnection device based on the proposed topology and control strategy can effectively compensate the pressure difference of the connecting points in the distribution network, regulate the power flow of the active distribution network, and realize the interconnection and mutual assistance of the distribution network.